Molecular detection of herpesvirus in a skin lesion of a humpback whale (Megaptera novaeangliae) from the Western Mediterranean Sea - Vargas Castro, Ignacio; Crespo-Picazo, José Luis; Jiménez Martínez, María De Los Ángeles; Muñoz-Baquero, Marta; Marco-Cabedo, Vicente; García-Párraga, Daniel; Sánchez-Vizcaíno Rodríguez, José Manuel (European Journal of Wildlife Research, 2024)
Author contributions: IVC wrote the manuscript, and JLCP, MAJM, MMB, VMC, DGP and JMSV helped revise it. JLCP, MMB and VMC performed external examination and collected samples. IVC performed molecular analysis and performed phylogenetic study. MAJM contributed by performing the histopathology analysis. DGP and JMSV coordinated and reviewed data collection, data analysis and manuscript writing. All authors read and approved the fnal manuscript. Herpesvirus has the potential to infect a wide variety of animal species. In cetaceans, Alpha- and/or Gammaherpesvirinaehave been identified in eight families of odontocetes, and one family of mysticetes. In May 2022, an adult humpback whale (Megaptera novaeangliae) was found stranded in Valencia, Spain. The whale was emaciated, in poor body condition, with multiple lacerations on the dorsal fin and a high number of epibionts of the Cyamidae family, known as whale lice. The individual had been previously released from a ghost net entanglement 5 days before becoming stranded. In a closer examination, various skin lesions were observed, including chronic, proliferative, and erosive dermatitis and a large ulcer extending to the deep dermis. As part of the infectious disease surveillance programme, molecular testing was performed on skin samples for herpesvirus, cetacean morbillivirus, and poxvirus. A positive result for herpesvirus was obtained from one of the skin lesions. The sequence was found to belong to the Alphaherpesvirinae subfamily, and it was closely related to alphaherpesvirus sequences from a fin whale (Balaenoptera physalus) and a humpback whale. Cetacean morbillivirus and poxvirus testing was negative. To the authors’ knowledge, this is the first report of herpesvirus in a humpback whale from the Mediterranean Sea. Reports on herpesvirus detection or infection in humpback whales (only species within the genus Megaptera) are scarce. In consequence, future virological assessments of humpback whales should include testing for herpesvirus. Consejo Superior de ...